Optical characterization of antimonene nanofilms deposited by low power sputtering - Lee, Quan Ken (Nanyang Technological University, 2020)
Antimonene, an atomic monolayer of antimony (Sb), is predicted to have high mobility and stability which are suitable for next generation electronics, optoelectronics and energy devices. Antimonene is known to be stable at room temperature and is less reactive than phosphorene, which is the reason why there are much more scientific interest in the material in the recent years. In this project, antimonene nanofilms were deposited using the low power sputtering system. Parameters, such as deposition time and temperature, were explored to optimize the deposition recipes. Samples of antimonene nanofilms were subjected to characterization for the thickness and optical properties. The changes in thickness profiles of the samples were characterized via atomic force microscope, while the structural changes were characterized through Raman spectroscopy and the optical properties were characterize via Ellipsometry.